Radiation Effects in Diamond pHEMTs. (3rd July 2019) - Thapa, Aayush; Shahin, David; Christou, Aris
Abstract : Field effect transistors (FET) based on diamond have 2-dimensional hole gas (2DHG) as conduction channel. In terms of usability in harsh environment, an important aspect of diamond-based FETs is its promise of radiation hardness. Two different types of radiation were used. A cyclotron was used for proton irradiation on diamond substrates, and a high capacity dry cell, panoramic gamma irradiator with 60 Co as source material was used for gamma irradiation on diamond-based FETs. Diamond substrates were irradiated with protons at 152 keV and fluence of 10 12 particles/cm 2 .